Some organisational and legal aspects of limiting the impact on the climate - Balashenko, Siarhei A. (Journal of the Belarusian State University. Law, 2023)
In the legal literature, the issues of legal regulation of relations in the field of climate change and climate protection have become the subject of thorough research relatively recently. Scientists support the idea of an inseparable link between climate issues and problems of ambient air protection, environmental protection and the handling of chemical substances. Modern legal literature notes the extreme urgency of effective legal regulation of relations in the field of combating climate change and concludes the importance of a comprehensive approach in the formation of the legal climate protection mechanism. The following priority areas for research in the field of legal regulation are considered study of the prospects for stimulating low-carbon economics activities through tax measures, establishment of a framework for the implementation of green public and other procurement to increase the interest of economic entities, citizens in the organisation of production and domestic activities on low-carbon economics principles, development of a system of legal and organisational measures for the use of energy consumption level labeling of goods, based on its energy efficiency.
Keywords: legal climate protection; ambient air protection; environmental protection; legal climate protection mechanism; climate protection law